PRESTASI AKADEMIK SISWA DITINJAU DARI PROKRASTINASI DAN PERSEPSI ANAK PADA POLA ASUH ORANG TUA DI SMK MUHAMMADIYAH 3 YOGYAKARTA - Latiffah Yunia Anggraini; Titik Muti'ah (Universitas Sarjanawiyata Tamansiswa, 2012)
ABSTRACTThe objective of the study is to determinethe influence of procrastination and childperceptionon parenting to the student achievementat 3thSMK Muhammadiyah Yogyakarta. As additional, the syle of parenting was assessed in improving student academic achievement. The subjects of the research are the students in the grade eleven at 3thSMK Muhammadiyah Yogyakarta. The method used in this research is regression analysis. The results of this research shows the relation of procrastination and the perception of the child on parenting to the student achivement was not significant in the meanwhile the influence of procrastination (p: 0, 000) and child perception on democratist parenting (p:0,031) to the student achivement showed significant result. The determination coefficient (R2) of this research was 0.622. As concludedon the procrastination and child perception on democratic parenting contributed amoung 62,2% of the influence to the academic achievement.Â Keyword : Procrastination,perception of the child on parenting, academic achievement.